Age-associated accumulation of B cells promotes macrophage inflammation and inhibits lipolysis in adipose tissue during sepsis - Anna Carey; Katie Nguyen; Pranathi Kandikonda; Victor Kruglov; Claire Bradley; Korbyn J.V. Dahlquist; Stephanie Cholensky; Whitney Swanson; Vladimir P. Badovinac; Thomas S. Griffith; Christina D. Camell (Cell Reports, 2024)
Summary: Non-canonical lipolysis induced by inflammatory cytokines or Toll-like receptor ligands is required for the regulation of inflammation during endotoxemia and sepsis. Canonical lipolysis induced by catecholamines declines during aging due to factors including an expansion of lymphocytes, pro-inflammatory macrophage polarization, and an increase in chronic low-grade inflammation; however, the extent to which the non-canonical pathway of lipolysis is active and impacted by immune cells during aging remains unclear. Therefore, we aimed to define the extent to which immune cells from old mice influence non-canonical lipolysis during sepsis. We identified age-associated impairments of non-canonical lipolysis and an accumulation of dysfunctional B1 B cells in the visceral white adipose tissue (vWAT) of old mice. Lifelong deficiency of B cells results in restored non-canonical lipolysis and reductions in pro-inflammatory macrophage populations. Our study suggests that targeting the B cell-macrophage signaling axis may resolve metabolic dysfunction in aged vWAT and attenuate septic severity in older individuals.